ANALYSIS OF FINANCIAL PERFORMANCE: A STUDY ON MANUFACTURING COMPANIES IN INDONESIA BEFORE AND AT THE BEGINNING OF THE COVID-19 PANDEMIC - Firdaus Hamta; Rahman Hasibuan; Muhammad Ikhlash; Bayu Efendi; Praida Hansyah; Ade Parlaungan Nasution (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2022)
The objective of this research was to explore the financial performance of manufacturing companies that registered on the Indonesia Stock Exchange in 2017-2020. The focuses of financial performance investigated were the ratio of profitability, activity and liquidity. The research was conducted at Supreme Cable Manufacturing and Commerce, Sky Energy Indonesia, and Satnusa Persada. A quantitative descriptive method was adopted in the electronics and cable sub-sector manufacturing unit to achieve the objective. The research found that the company's financial performance at the beginning of the Covid-19 pandemic in 2020 was better than before the pandemic in 2017-2019. It was revealed that the profitability ratio fell in 2019, which was influenced by capital in 2017 and 2019 and increased in 2020. The activity ratio improved in 2019 and 2020 due to receivables turnover in utilizing assets to generate profit. The liquidity ratio was relatively good in 2020 by the average value of 2 times better than before. While in 2017 to 2019, the results showed that the average value was two times lower.